(untitled) (Scientia Agricola, 2009)
Land use change and land management practices can modify soil carbon (C) dynamics and soil fertility. This study evaluated the effect of tillage systems (no-tillage - NT and conventional tillage - CT) on soil C and nutrient stocks in an Oxisol from an Amazonian cerrado following land use change. The study also identified relationships between these stocks and other soil attributes. Carbon, P, K, Ca and Mg stocks, adjusted to the equivalent soil mass in the cerrado (CE), were higher under NT. After adoption of all but one of the NT treatments, C stocks were higher than they were in the other areas we considered. Correlations between C and nutrient stocks showed positive correlations with Ca and Mg under NT due to continuous liming, higher crop residue inputs and lack of soil disturbance, associated with positive correlations with cation exchange capacity (CEC), base saturation and pH. The positive correlation (r = 0.91, p < 0.05) between C stocks and CEC in the CE indicates the important contribution of soil organic matter (SOM) to CEC in tropical soils, although the exchange sites are - under natural conditions - mainly occupied by H and Al. Phosphorus and K stocks showed positive correlations (0.81 and 0.82, respectively) with C stocks in the CE, indicating the direct relationship of P and K with SOM in natural ecosystems. The high spatial variability of P and K fertilizer application may be obscuring these soil nutrient stocks. In this study, the main source of P and K was fertilizer rather than SOM.